The Role of Artificial Intelligence in E-Government and Its Implications for Indonesia's Economic Growth - Hasbi; Asgar (www.amertainstitute.com, 2024)
E-Government has become an important milestone in the modernization of government administration and public services. In Indonesia, the development of E-Government has been regulated through the Instruction of the President of the Republic of Indonesia Number 3 of 2003 concerning National Policy and Strategy. Implementation stages of E-Government in Indonesia includes development of information and communication technology infrastructure, application development E-Government, application integration E-Government, service-based application development, to community-based application development. The use of artificial intelligence (AI) in E-Government reflects the government's efforts to improve public services with higher efficiency. The method used to collect research data is a literature review and data analysis techniques using a qualitative approach. The research results show that there is great potential in utilizing artificial intelligence to increase government efficiency and responsiveness in providing better public services for citizens, and have implications for Indonesia's economic growth. E-Government is able to support sustainability both from economic, social and environmental aspects, but further research and adequate regulations are needed to support the implementation of AI in E-Government in order to provide maximum benefits.